Identifikasi Deforestasi di Provinsi Kalimantan Timur Tahun 1990 dan 2020 Menggunakan Sistem Informasi Geografis - Andriani Nadia Rahmawati; Feri Fadlin; Suparjo Suparjo; Nia Kurniadin (Journal of Geomatics Engineering, Technology, and Science, 2024)
This research is motivated by the abundance of resources available in Indonesia's forests. However, it is undeniable that the forest resources in Indonesia have a promising economic function, particularly in the form of timber or tree trunks that hold economic value, leading to timber exploitation that can result in deforestation. One example of this is the deforestation occurring in East Kalimantan Province, where both production forest areas and protected forest areas are experiencing gradual deforestation each year. This study aims to understand land use and identify deforestation in East Kalimantan Province in the years 1990 and 2020. The method used in this research is Geographic Information System (GIS) to process and analyze data, thereby obtaining information on land use types, area, and deforestation in East Kalimantan Province for the years 1990 and 2020. The results of this research include maps and data on deforestation in East Kalimantan Province for the years 1990 and 2020. Land use in East Kalimantan Province is classified into 21 land use classes, namely primary dryland forest, secondary dryland forest, primary mangrove forest, secondary mangrove forest, primary swamp forest, secondary swamp forest, plantation forest, plantations, shrubland, swamp shrubland, mixed dryland agriculture with shrubs, dryland agriculture, transmigration areas, settlements, open land, rice fields, ponds, water bodies, swamps, airports, and mining. There are four dominant land use change types related to deforestation: first, four types of forest land have changed to swamp shrubland; second, two types of forest land have changed to mixed dryland agriculture with shrubs; third, two types of forest land have changed to ponds; and fourth, two types of forest land have changed to mining.